Thermal-hydraulic performance of a tapered microchannel - Cheng, Kai Xian (2020)
Tapered microchannel is a channel configuration design (CCD) which has gained attention owing to the superior performance in promoting uniform temperature distribution in a microchannel. In this study, the thermal-hydraulic performance of four different tapered channels is evaluated against a straight microchannel. The average hydraulic diameter, conductive heat transfer in the substrate material and convective heat transfer area are kept constant for the microchannels. The experiment is conducted for steady-state convective heat transfer using distilled water as the working fluid for Reynolds number range of 1300–3400 and a constant heat flux of 53.0 W/cm2. Results show that highly-tapered microchannels promote early turbulence at lower Reynolds numbers with better heat transfer and much greater pressure drop. All the tapered microchannels possess a thermal-hydraulic performance index which is less than 1, implying that a tapered microchannel yields a lower heat transfer capability given the same pumping power as a straight microchannel.